A prospective study of outcome and monitoring of patients with perforation peritonits by using APACHE 2 score - Gupta, R. S.; Roshan, Santosh; Pandey, Vishnukant; Shrivastava, Surendra (International Surgery Journal, 2021)
Background: Perforation peritonitis is very common surgical emergency and despite newer and advanced technology as a monitoring system APACHE 2 score have a good predictive power to predict outcome and monitoring in such patient Methods: This is a prospective study by which APACHE 2 score was applied over the patient before the surgery and after the surgery at first post operative day and score was calculated in selected preformed and result was concluded Results: The outcome of the Patients largely depends on age, perforation size, duration of presentation, and duration of hospitalization all these are well correlated with APCHE 2 score to predict outcome and monitoring. Conclusions: The accuracy of APACHE 2 score to predict the outcome in perforation peritonitis increases when the result of score was combined which was applied two time prior to surgery and after the surgery.